Self-confidance in performing among music students Faculty Of Music at UiTM / Carol S. Sumail - S. Sumail, Carol (Faculty of Music, 2011)
This study aimed to investigate the factors which contributed to students' low self-confidence in during music performances, how low self-confidence affected student performances and to find out how students improved their self-confidence in musical performance at the Faculty of Music in UiTM Shah Alam. The respondents of this study were 100 music comprising of 50 males and 50 females. Questionnaires were distributed to the students at random. Findings showed that a majority of subjects from all programs felt moderately high confidence when performing on their major instrument (Total Mean = 6.80, SD=1645j. It appears that all subjects felt their lack of self-confidence has affected their performances and a majority of subjects (n=95) reported "nervousness", "lack of practice" and "fear of failure" as the main factors that contributed to their low self-confidence. Students said that having enough practice on their instrument was their way to overcome low self-confidence during performances followed by warming up before performances.